Menalar Indikator yang Berkorelasi Terhadap Penerapan Tax Haven - Benyamin Melatnebar Wuarmanuk; Yunia Oktari; Kito Kurniawan; Eugenius Laluur (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2022)
This study uses the variables of transfer pricing, intangible assets, management compensation, and multinational companies to focus on the factors that influence the use of tax havens. This study aims to determine the determinants of the use of related companies in tax havens, specifically this study uses secondary data, namely the annual reports of all non-financial companies listed on the Indonesia Stock Exchange and subsidiaries listed in tax havens. 2017. This is a quantitative study using multiple regression analysis. The results of this study indicate that active transfer pricing activities and management compensation have a positive impact on the utilization of related companies in tax havens. The high activity of intangible assets and multinational companies does not have a significant impact on the utilization of related companies in the tax haven. The results of this study are to determine the indicators of the use of companies associated with taxpayers. Based on the results of the delay test, it is concluded that the operation of violent price transfers and management compensation has a positive effect on the use of affiliated companies in tax havens. The high performance of intangible assets and international companies has no significant impact on the use of affiliated companies in tax havens. The results of this study indicate the effect of transfer prices and management on the use of affiliated companies in tax havens. The results of this study can create a map of the company's behavior identified in the tax relationship